Family problem solving interactions and 6-month symptomatic and functional outcomes in youth at ultra-high risk for psychosis and with recent onset psychotic symptoms: A longitudinal study - O'Brien, Mary P. (2008)
This study prospectively examined the relationship between social problem solving behavior exhibited by youths at ultra-high risk for psychosis (UHR) and with recent onset psychotic symptoms and their parents during problem solving discussions, and youths' symptoms and social functioning six months later. Twenty-seven adolescents were administered the Structured Interview for Prodromal Syndromes and the Strauss-Carpenter Social Contact Scale at baseline and follow-up assessment. Primary caregivers participated with youth in a ten minute discussion that was videotaped, transcribed, and coded for how skillful participants were in defining problems, generating solutions, and reaching resolution, as well as how constructive and/or conflictual they were during the interaction. Controlling for social functioning at baseline, adolescents' skillful problem solving and constructive communication, and parents' constructive communication, were associated with youths' enhanced social functioning six months later. Controlling for symptom severity at baseline, we found that there was a positive association between adolescents' conflictual communications at baseline and an increase in positive symptoms six months later. Taken together, findings from this study provide support for further research into the possibility that specificfamily interventions, such as problem solving and communication skills training, may improve the functional prognosis of at-risk youth, especially in terms of their social functioning.